An Integrated Learning Model Based on the Tri Hita Karana Philosophical Concept in Improving Cultural Literacy - I Wayan Ade Yantika; I Wayan Suja; Ida Bagus Putu Arnyana (Journal of Education Reseach and Evaluation, 2026)
This research is motivated by the low level of cultural literacy among students, as indicated by their lack of understanding, attitudes, and practices of local cultural values in daily life. Furthermore, the learning process in schools has not optimally integrated the Tri Hita Karana philosophical concept. This study aims to analyze the effects of Tri Hita Karana-based learning models on students' cultural literacy in elementary schools. This study used a pretest-posttest control-group design, involving fifth- and sixth-grade students from several elementary schools in Bali. The experimental group received Tri Hita Karana-based learning models, while the control group followed conventional learning. Data were obtained through cultural literacy tests, observations, and interviews with students and teachers. The results showed that the experimental group experienced a significant increase in cultural literacy compared to the control group. Tri Hita Karana-based learning not only improves students' local cultural knowledge but also shapes better student character, including a sense of responsibility, empathy, and concern for the environment. This study concludes that applying the Tri Hita Karana philosophy in elementary school learning can enrich cultural literacy and strengthen students' character. It has the potential to serve as an effective model for culture-based education in Indonesia. Consequently, implementing an integrated learning model grounded in the Tri Hita Karana philosophical concept can serve as a reference for teachers and schools in designing contextual, meaningful learning experiences to improve students' cultural literacy.